Histopathological and Hematological Alterations in Red Mullet (Mullus barbatus) Induced by Heavy Metal Pollution in Sousa Port, Libya - Nagi Mousa; Salama I Ahmadi; Yaser Hamad; Abdulrahman Aljali (Libyan Journal of Medical and Applied Sciences, 2025)
Heavy metals pollution of seawater is a major environmental concern, affecting the aquatic environment and fish health. The current study focused on the levels of selected heavy metals (iron, copper, lead, and cadmium) in the water, gill, liver, and kidney tissues of (Mullus barbatus) fish collected from the port of Sousa, Libya, during years 2024-2025, and recorded the associated histopathological and hematological changes. Water analysis revealed elevated concentrations of lead (0.67 mg/L) and iron (5.09 mg/L), exceeding the permissible limits set by the world health organization (WHO). These concentrations indicate significant contamination. The results also showed higher levels of iron and copper in the liver, while lead and cadmium were more concentrated in the kidney. The histopathological screening of gills revealed hyperplasia of secondary lamellae and dense inflammatory cell infiltration, the liver showing hepatocyte vacuoles, cytoplasmic degeneration, and lipid accumulation in the liver, as well as tubular degeneration and an increase in hematopoietic cells in the kidney, reflecting heavy metal-induced organ toxicity. Blood analysis appeared elevated hemoglobin (Hb) and hematocrit (Ht) levels, along with a severe decrease in Thrombocytes count (TCs), denoting physiological stress and impaired hematopoiesis. The results confirm that the M. barbatus fish is an effective biomarker for heavy metal pollution and highlight the environmental and potential public health risks associated with environmental pollution in Libyan coastal waters.